Sustaining Superior Performance in Business Ecosystems: Evidence from Application Software Developers in the iOS and Android Smartphone Ecosystems - Kapoor, Rahul; Agarwal, Shiva (Organization Science, 2017)
We study the phenomenon of business ecosystems in which platform firms orchestrate the functioning of ecosystems by providing platforms and setting the rules for participation by complementor firms. We develop a theoretical framework to explain how the structural and evolutionary features of the ecosystem may shape the extent to which participating complementor firms can sustain their superior performance. The structural feature, which we refer to as ecosystem complexity, is a function of the number of unique components or subsystems that interact with the complementor’s product. We incorporate the evolutionary features by considering the role of generational transitions initiated by platform firms over time as well as the role of complementors’ ecosystem-specific experience. Evidence from Apple’s iOS and Google’s Android smartphone ecosystems supports our arguments that higher ecosystem complexity helps app developers sustain their superior performance, and that this effect is stronger for more experienced firms. In contrast, platform transitions initiated by Apple and Google make it more difficult for app developers to sustain their performance superiority, and that this effect is exacerbated by the extent of ecosystem complexity. The study offers a novel account of how the performance of complementor firms in platform-based business ecosystems may be shaped by their ecosystem-level interdependencies.